BIM for construction safety improvement in Gaza strip: awareness, applications and barriers. Issue 3 (2nd July 2016) - Enshassi, Adnan; Ayyash, Abed; Choudhry, Rafiq M.
Abstract : The objectives of this paper are to elicit the perception of contracting parties regarding building information modelling (BIM), the most important safety-related applications of BIM and the barriers to adopting BIM in the local construction industry. Data for this study were collected through a questionnaire survey. A total of 75 questionnaires were randomly distributed to contractors, owners and consultants, and 37 were returned, representing a 49% response rate. The findings indicated that 33% of the respondents had no knowledge of the concept of BIM, 28% of the respondents' organizations are not using BIM and if used it was implemented to a limited extent. The results indicated that 'hazard identification and minimization' and 'safety training and education' are the most important safety-related applications provided by BIM tools to improve safety performance in construction. Lack of universal use in the construction sector and insufficient training availability are the highest ranked barriers to adopting BIM in construction to improve safety. The research results may assist BIM developers to introduce the best applicable tools to improve safety performance in the construction industry. It is recommended that training courses be conducted regarding BIM concept and the benefits of its application in the construction industry.